2022
DOI: 10.3390/ma15228169
|View full text |Cite
|
Sign up to set email alerts
|

A New Insight into the Mechanisms Underlying the Discoloration, Sorption, and Photodegradation of Methylene Blue Solutions with and without BNOx Nanocatalysts

Abstract: Methylene blue (MB) is widely used as a test material in photodynamic therapy and photocatalysis. These applications require an accurate determination of the MB concentration as well as the factors affecting the temporal evolution of the MB concentration. Optical absorbance is the most common method used to estimate MB concentration. This paper presents a detailed study of the dependence of the optical absorbance of aqueous methylene blue (MB) solutions in a concentration range of 0.5 to 10 mg·L−1. The nonline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…As we know, MB degradation increases as irradiation time is prolonged, along with a decrease in MB concentration. Matveev et al [35] used optical absorbance to estimate MB concentration, and found that aqueous MB solutions have a nonlinear behavior of optical absorbance, suggesting the formation of MB dimers and trimers in the specific concentration range. MB monomers and dimers may be involved in different kinds of photodynamic reactions, and their concentration influences the mechanisms and types of ROS produced [36].…”
Section: Discussionmentioning
confidence: 99%
“…As we know, MB degradation increases as irradiation time is prolonged, along with a decrease in MB concentration. Matveev et al [35] used optical absorbance to estimate MB concentration, and found that aqueous MB solutions have a nonlinear behavior of optical absorbance, suggesting the formation of MB dimers and trimers in the specific concentration range. MB monomers and dimers may be involved in different kinds of photodynamic reactions, and their concentration influences the mechanisms and types of ROS produced [36].…”
Section: Discussionmentioning
confidence: 99%
“…Semiconductor photocatalysis is deemed as a promising technique to purify water which is contaminated by various pollutants, such as dyes, antibiotics, endocrine disruptors, and so on [ 1 , 2 , 3 ]. Taking full advantage of solar energy has already been proven as a “green” strategy to settle environmental contamination and energy crunch [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such advanced materials can be also used for electrocatalytic applications involving the oxygen evolution reaction (OER) [ 12 ] and the electrocatalytic reduction of carbon dioxide (CO 2 RR) [ 15 ]. Researchers’ attention has been especially drawn to environmental protection, where advanced materials and adsorbents are highly demanded for the processing of waste components [ 1 , 16 , 17 , 18 ] and pharmaceuticals [ 17 ], the (photo)degradation of dyes [ 16 , 18 ], the catalytic decomposition of chlorinated hydrocarbons [ 1 , 2 , 4 ], wastewater treatment [ 1 , 18 ], and the abatement of CO-containing gases [ 13 ].…”
mentioning
confidence: 99%
“…In the research presented in [ 18 ], the authors synthesized zerovalent iron (ZVI) using biological reducing agents isolated from tea-leaves (polyphenolic compounds) and showed the applicability of the designed ZVI system to wastewater treatment. In [ 16 ], the photodegradation of methylene blue over BNO x catalysts (containing 4.2 and 6.5% oxygen) was studied in detail. The authors revealed the important role of surface oxygen defects in the adsorption capacity and photocatalytic activity of BNO x .…”
mentioning
confidence: 99%